Um mar de imagens: representações imagéticas do município de Torres (1930-1960) - Eberhardt, Camila (Universidade do Vale do Rio dos Sinos, 2018)
The thesis "A Sea of Images: Imaginary Representations of the municipality of Torres (1930-1960)" seeks to identify the different images that were produced about Torres, besides the traditional representation of what Torres means beach and, thus, to know the history and the memory of the municipality during this period between 1930 and 1960. For this purpose, the present thesis analyzes two collections of images: the Collection of Images and Sounds developed by Ulbra, Campus Torres, which has 2,647 photographs; and the collection of the House of Culture, organized by the municipality of Torres, which has 1,100 photographs. In this way, we work with visual themes that were created to meet the complexity of the collections, do not restrict the analysis to the city only, but also enter the territories belonging to the interior of the municipality. The work carried out by the photographic studio Feltes was observed in the course of the research because it comprised an important photographic studio in the municipality of Torres between the years of 1930 to 1960. At the same time, we analyzed the Globe Magazine that acted between the years of 1929 to 1967. Through the magazine, we can understand the representations about beach and joy that in numerous reports were adjectives destined to Torres beach. The images made in the municipality of Torres between the years 1930 and 1960 and preserved through the analyzed collections, together with the reports of the Globe Magazine, allowed the understanding of the history and memory of the municipality in which different socio-cultural aspects were present.
Keywords: Fotografia; Torres; Veraneio; Praia; Rural; Representação; Photography; Torres; Summer; Beach; Rural; Representativo; ACCNPQ::Ciências Humanas::História